Pengembangan Essence dari Ekstrak Kayu Secang (Caesalpinia sappan L.) - Lidya Ameliana; Budipratiwi Wisudyaningsih; Dwi Nurahmanto; Yenika Ayu Mega Dianatri (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Sappan wood (Caesalpinia sappan L.) was reported to have natural antioxidant properties. Brazillin is the compound responsible for its antioxidant effect. Antioxidants are needed to prevent premature aging of the skin. Essence is a cosmetic that contains topical antioxidants. Essence has advantages over other skincare products, and essence is easier to absorb into the skin. The objective of the present study was to optimize and evaluate the Essence of sappan wood ethanolic extract for treatment as a cosmetic antioxidant. Simplex lattice design was adopted to evaluate the effect of butylene glycol and glycerin concentration on Essence characteristics. The method used in the extraction is maceration with ethanol solvent. The results showed that both butylene glycol and glycerin significantly enhanced the viscosity and pH value of the sappan essence formulation. The optimum Essence formula consisted of 10% butylene glycol with a predicted viscosity value of 2,944 dPas and a pH of 5,075. The characteristics of the optimum formula of sappan wood extract Essence have a thick texture, a characteristic odor of colored extract brownish yellow, homogeneous, and has a spreadabillity of 14 cm.